Effectiveness of exercise therapy in patients with knee osteoarthritis: an overview of systematic reviews - Daisuke Sasaki; Takashi Kitagawa; Yuichi Isaji; Kunihiro Onishi; Masateru Hayashi; Wataru Okuyama (BMJ Open)
Objective This study aimed to assess the methodological quality of published systematic reviews of exercise therapy in knee osteoarthritis and summarise their reported effectiveness on quality of life, knee joint function, or adverse events.Design Overview of systematic reviews.Data sources PubMed, Embase, CINAHL, Web of Science and CENTRAL (searched on 14 April 2025), plus grey literature (PROSPERO, Epistemonikos, OpenGrey).Eligibility criteria for selecting studies We included systematic reviews of randomised controlled trials in patients diagnosed with knee osteoarthritis by imaging or clinical criteria and treated conservatively with exercise therapy; we excluded reviews that enrolled patients scheduled for surgery, with acute inflammation or osteoarthritis of other joints (hand, hip, ankle), for which relevant author data could not be obtained after one contact attempt, or that did not report at least one primary outcome (quality of life, knee joint function or adverse events).Data extraction and synthesis Two reviewers independently extracted data on study characteristics, interventions and outcomes, and assessed methodological quality using the AMSTAR 2 (A MeaSurement Tool to Assess systematic Reviews 2) tool. Due to heterogeneity in outcome measures across systematic reviews, meta-analysis was not conducted. Effectiveness was defined as any reported beneficial outcome of exercise therapy on predefined outcomes, including quality of life, physical function, pain or adverse events.Results 58 systematic reviews were selected. Muscle-strengthening (74.1%) and aerobic (48.2%) exercises were the most commonly prescribed exercise-based interventions. SF-36 (36-Item Short Form Health Survey) and the WOMAC (Western Ontario and McMaster Universities Osteoarthritis Index) were the most popular outcome-evaluation tools. Furthermore, 63.7% of the systematic reviews revealed that exercise therapy improved all outcomes. The number of intervention-related adverse events was small. Notably, almost all systematic reviews (87.4%) had a critically low quality.Conclusions Current evidence on exercise therapy for knee osteoarthritis is inadequate. Nevertheless, exercise therapy can be considered for conservative treatment of knee osteoarthritis. Future studies should use network meta-analyses to compare the effects of different exercise therapies and determine their superiority over other conservative therapies.